1994
DOI: 10.1063/1.467712
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of velocity-aligned atoms probed by Doppler profiles: H+O2→OH+O

Abstract: Final state resolved vector properties of the reaction H (2S)+O2(3Σ−g)→OH(2Π)+O(3P) have been measured using Doppler spectroscopy. Velocity-aligned H atoms were generated by photodissociation of H2S with linearly polarized ArF excimer laser light. The correlated velocity and angular momentum distribution of nascent OH reaction products was probed by laser induced fluorescence. Techniques are described for analyzing the line shapes, modeling the bipolar moments of the OH velocity and angular momentum distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 72 publications
3
82
0
Order By: Relevance
“…Therefore, using the symmetry of the Clebsch-Gordan coefficient in Eq. (17), one can see that in case Q r = 0 the differential cross section can differ from zero only when the rank K r is also even. This feature nicely fits with the known fact 45 that only the component of the reactant angular momentum orientation perpendicular to the reaction plane can contribute to the differential reaction cross section, see Eq.…”
Section: B Differential Cross Section For Bimolecular Chemical Reactmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, using the symmetry of the Clebsch-Gordan coefficient in Eq. (17), one can see that in case Q r = 0 the differential cross section can differ from zero only when the rank K r is also even. This feature nicely fits with the known fact 45 that only the component of the reactant angular momentum orientation perpendicular to the reaction plane can contribute to the differential reaction cross section, see Eq.…”
Section: B Differential Cross Section For Bimolecular Chemical Reactmentioning
confidence: 95%
“…The DCS for Li + HF(v r = 0, j r = 3) → LiF(v, j ) + H reaction at 317 meV has been calculated using Eq. (17) and are shown in Fig. 2.…”
Section: LI + Hf Chemical Reactionmentioning
confidence: 99%
“…These techniques motivate the interest to measure features of the k-kЈ -JЈ distribution in probing the product state selective dynamics of photoninitiated bimolecular reactions and have been successfully exploited by a number of groups to determine product stateselective differential cross sections with high precision. 16,17 Measurements have been performed either under thermal conditions 18,19 or, with potentially higher collision energy and angular resolution, under jet cooled expansion conditions. [20][21][22] The enhanced reagent number densities achieved using these techniques, compared with those typically obtained in conventional crossed-molecular beam methods, have now enabled full state-to-state differential cross sections to be measured for the ClϩCH 4 reaction.…”
Section: Aϩbc→abϩc ͑1͒mentioning
confidence: 99%
“…The measurement of product polarization as a function of scattering angle has been achieved with the development of photoloc method. [33][34][35][36][37] Most recently, Li 38 employed the QCT method to study the vector correlations between the product and reagent for the title reaction occurred on the 1A′ DK PES. They found that the OH products are produced mainly in the plane of H-O-H plane.…”
Section: Introductionmentioning
confidence: 99%